On the multiple roles of the voltage gated sodium channel β1 subunit in genetic diseases - Baroni, Debora; Moran, Oscar (Frontiers in Pharmacology, 2015)
Voltage-gated sodium channels are intrinsic plasma membrane proteins that initiate the action potential in electrically excitable cells. They are composed of a pore-forming α-subunit and associated β-subunits. The β1-subunit was the first accessory subunit to be cloned. It can be important for controlling cell excitability and modulating multiple aspects of sodium channel physiology. Mutations of β1 are implicated in a wide variety of inherited pathologies, including epilepsy and cardiac conduction diseases. This review summarizes β1-subunit related channelopathies pointing out the current knowledge concerning their genetic background and their underlying molecular mechanisms.